High-strength, corrosion-resistant glass-lined materials for chemical reactors
By adjusting the formulation composition of glass lined materials, introducing specific oxides and borates and other components, the physical and chemical properties of glass lined bottom glaze are optimized, and the shortcomings of existing bottom glazes in mechanical strength and acid and alkali corrosion resistance are solved, and higher mechanical strength and corrosion resistance are achieved.
Patent Information
- Application Number
- CN202411082815.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-08
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-08-08
AI Technical Summary
The existing glass-lined bottom glazes still have room for improvement in mechanical strength and acid-base corrosion resistance, especially in terms of low-temperature tightness, scattering tendency, reboiling temperature, foaming temperature, bubble structure, expansion coefficient, firing amplitude and rheology of glaze slurry.
By adjusting the formula composition of glass lined materials, introducing components such as TiO2, SrO, HfO2, Li2B4O7, etc., the physical and chemical properties of the base glaze are optimized.
It significantly improves the mechanical strength and acid-base corrosion resistance of glass-lined bottom glazing, and improves its application performance in chemical reactors.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of glass-lined materials, and in particular relates to a high-strength, corrosion-resistant glass-lined material for chemical reactors. Background Art
[0002] Glass-lined equipment is a glassy enamel made of silicon dioxide as the main body and other elements. After multiple high-temperature sintering at 920~960℃, the enamel is firmly attached to the surface of the metal iron tire. Therefore, it has both the chemical stability similar to glass and the dual advantages of metal strength, and is an excellent corrosion-resistant equipment. It is widely used in industrial production and scientific research such as chemical industry, petroleum, metallurgy, medicine, pesticides, dyes, synthetic rubber, synthetic fibers, plastics, food and beverages, and defense industry for reactions, evaporation, concentration, synthetic polymerization, saponification, sulfonation, chlorination, nitration, heat exchange, separation, metering, storage, etc., to replace stainless steel and non-ferrous metal equipment, with excellent comprehensive performance.
[0003] Glass-lined glaze is the main raw material for manufacturing glass-lined equipment. The quality and technical level of glass-lined glaze have an important impact on the service life of glass-lined equipment. Glass-lined glaze is divided into base glaze and top glaze. The base glaze forms an interpenetration layer with the surface of the steel plate, which is the basis of the overall structure of the glass-lined glaze.
[0004] In the prior art, the performance of the base glaze still needs to be improved in the following aspects: First, the adhesion strength, especially the low-temperature adhesion strength. Poor adhesion strength will cause the base glaze to fall off and explode. Second, the tendency to scale. The more micropores in the base glaze layer, the stronger its anti-scale. Introducing oxides that can produce gas into the base glaze, refractory components such as sodium carbonate, molybdate, silicon oxide, zirconium oxide, etc., increase the micropores and air permeability of the base glaze layer. Third, the reboiling temperature. The reboiling is manifested on the porcelain surface in the form of bubbles. After firing and cooling at a certain temperature, the firing time is extended for the second time than the first time to observe the changes in the bubbles (number and size). The denser and larger the bubbles, the more serious the reboiling tendency. Fourth, the foaming temperature, which refers to the temperature at which the gas is most intensely generated when the base glaze is fired. The glaze viscosity corresponding to this temperature is 10 6 The foaming is not obvious, indicating that the exhaust performance of the base glaze is good. The fifth is the bubble structure, including porosity, distribution uniformity, and bubble size. The structure with porosity <10% and small and uniformly distributed bubbles is reasonable. The sixth is the expansion coefficient. The expansion coefficient of the steel plate is 13×10 -6 The expansion coefficient of the base glaze is controlled at 9.5×10 -6 The seventh is the firing range. The wider the firing range, the better the quality of the base glaze, which can overcome the defects such as copper head and local burning produced during enameling. The eighth is the rheological properties of the glaze slurry, that is, the suspension performance and retention. Summary of the invention
[0005] The technical problem to be solved by the present invention is: how to further improve the mechanical strength and acid and alkali corrosion resistance of the glass-lined bottom glaze.
[0006] In order to achieve the above technical objectives, the present invention adopts the following technical solutions:
[0007] High-strength, corrosion-resistant glass-lined material for chemical reactors, including the following components by weight: Al 2 O 3 6~8 parts, SiO 2 68~72 copies, B 2 O 3 12~14 servings, Na 2 O 1~3 parts, K 2 O 2~3 parts, Li 2 O 0.8~1.5 parts, CaF 2 6~8 parts, HfO 2 0.8~1 parts, ZrO 2 8~9 parts, CoO 0.5~1 parts, NiO 2~3 parts, Li 2 B 4 O 7 0.4~0.8 parts, BaMoO 4 0.6~1 parts, Sb 2 O 3 1.2~2.2 parts, V 2 O 5 4~5 parts, TiO 2 4~6 parts, SrO 0.2~0.6 parts.
[0008] Preferably, the glass-lined material comprises the following components in parts by weight: Al 2 O 3 6.2 parts, SiO 2 69 copies, B 2 O 3 12.5 servings, Na 2 O 2.3 parts, K 2 O 2.7 parts, Li 2 O 1.1 parts, CaF 2 6.5 parts, HfO 2 0.95 parts, ZrO 2 8.4 parts, CoO 0.7 parts, NiO 2.2 parts, Li 2 B 4 O 7 0.66 parts, BaMoO 4 0.87 parts, Sb 2 O 3 1.7 parts, V 2 O 5 4.2 parts, TiO2 4.1 parts, SrO 0.3 parts.
[0009] Preferably, the glass-lined material comprises the following components in parts by weight: Al 2 O 3 7.2 parts, SiO 2 68.7 copies, B 2 O 3 13.2 servings, Na 2 O 2.6 parts, K 2 O 2.1 parts, Li 2 O 0.88 parts, CaF 2 6.2 parts, HfO 2 0.98 parts, ZrO 2 8.7 parts, CoO 0.62 parts, NiO 2.5 parts, Li 2 B 4 O 7 0.53 parts, BaMoO 4 0.67 parts, Sb 2 O 3 1.24 parts, V 2 O 5 4.6 parts, TiO 2 5.5 parts, SrO 0.33 parts.
[0010] Preferably, the glass-lined material comprises the following components in parts by weight: Al 2 O 3 7.9 parts, SiO 2 71.5 copies, B 2 O 3 12.8 servings, Na 2 O 1.5 parts, K 2 O 2.7 parts, Li 2 O 1.33 parts, CaF 2 6.52 parts, HfO 2 0.99 parts, ZrO 2 8.85 parts, CoO 0.83 parts, NiO 2.46 parts, Li 2 B 4 O 7 0.45 parts, BaMoO 4 0.71 parts, Sb 2 O 3 1.3 parts, V 2 O 5 4.8 parts, TiO 2 6 parts, SrO 0.2 parts.
[0011] Preferably, the glass-lined material comprises the following components in parts by weight: Al 2O 3 8 parts, SiO 2 69.3 copies, B 2 O 3 13.9 servings, Na 2 O 1.2 parts, K 2 O 2.2 parts, Li 2 O 1.46 parts, CaF 2 6.67 parts, HfO 2 0.91 parts, ZrO 2 8.2 parts, CoO 0.95 parts, NiO 2.5 parts, Li 2 B 4 O 7 0.6 parts, BaMoO 4 0.74 parts, Sb 2 O 3 1.73 parts, V 2 O 5 4.56 parts, TiO 2 4.24 parts, SrO 0.51 parts.
[0012] Preferably, the glass-lined material comprises the following components in parts by weight: Al 2 O 3 7.5 parts, SiO 2 71.8 copies, B 2 O 3 14 servings, Na 2 O 1.6 parts, K 2 O 2.7 parts, Li 2 O 1.1 parts, CaF 2 6.9 parts, HfO 2 0.81 parts, ZrO 2 8.9 parts, CoO 0.51 parts, NiO 2.93 parts, Li 2 B 4 O 7 0.65 parts, BaMoO 4 0.86 parts, Sb 2 O 3 1.77 parts, V 2 O 5 4.34 parts, TiO 2 5.62 parts, SrO 0.5 parts.
[0013] Preferably, the glass-lined material comprises the following components in parts by weight: Al 2 O 3 7 parts, SiO 2 70 copies, B 2 O 3 13 servings, Na 2O 2 parts, K 2 O 2.5 parts, Li 2 O 1.2 parts, CaF 2 7 parts, HfO 2 0.9 parts, ZrO 2 8.5 parts, CoO 0.75 parts, NiO 2.5 parts, Li 2 B 4 O 7 0.6 parts, BaMoO 4 0.8 parts, Sb 2 O 3 1.6 parts, V 2 O 5 4.5 parts, TiO 2 5 parts, SrO 0.4 parts.
[0014] Preferably, the glass-lined material comprises the following components in parts by weight: Al 2 O 3 7.2 parts, SiO 2 70.3 copies, B 2 O 3 12.8 servings, Na 2 O 2.5 parts, K 2 O 2.7 parts, Li 2 O 1.13 parts, CaF 2 7.3 parts, HfO 2 0.96 parts, ZrO 2 8.2 parts, CoO 0.9 parts, NiO 2.4 parts, Li 2 B 4 O 7 0.66 parts, BaMoO 4 0.76 parts, Sb 2 O 3 1.84 parts, V 2 O 5 4.87 parts, TiO 2 5 parts, SrO 0.21 parts.
[0015] Preferably, the glass-lined material comprises the following components in parts by weight: Al 2 O 3 6.5 parts, SiO 2 70.9 copies, B 2 O 3 13.7 servings, Na 2 O 1.6 parts, K 2 O 2.4 parts, Li 2 O 1 part, CaF 2 7 parts, HfO 2 0.91 parts, ZrO2 8.8 parts, CoO 0.79 parts, NiO 2.47 parts, Li 2 B 4 O 7 0.56 parts, BaMoO 4 0.87 parts, Sb 2 O 3 1.73 parts, V 2 O 5 4.22 parts, TiO 2 5.81 parts, SrO 0.36 parts.
[0016] Preferably, the glass-lined material comprises the following components in parts by weight: Al 2 O 3 7.6 parts, SiO 2 71.2 copies, B 2 O 3 14 servings, Na 2 O 2.98 parts, K 2 O 2.63 parts, Li 2 O 1.15 parts, CaF 2 7.3 parts, HfO 2 0.94 parts, ZrO 2 8.58 parts, CoO 0.92 parts, NiO 2.43 parts, Li 2 B 4 O 7 0.69 parts, BaMoO 4 0.66 parts, Sb 2 O 3 1.91 copies, V 2 O 5 4.64 parts, TiO 2 4.4 parts, SrO 0.53 parts.
[0017] The present invention provides a high-strength, corrosion-resistant glass-lined material for chemical reactors. The technical solution improves the formula of the glass-lined bottom glaze by introducing TiO 2 , SrO, HfO 2 , Li 2 B 4 O 7 The components significantly improve the physical and chemical properties of the glass enamel. The glass enamel base enamel constructed by the present invention has higher mechanical strength and better acid and alkali corrosion resistance, and has outstanding technical advantages. DETAILED DESCRIPTION
[0018] The technical solutions in the embodiments of the present application will be described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application. In addition, ordinary technicians in this field know that with the development of technology and the emergence of new scenarios, the technical solutions provided in the embodiments of the present application are also applicable to similar technical problems.
[0019] In the description of the present application, it should be understood that, unless otherwise defined, all technical and scientific terms used in the present application have the same meaning as those commonly understood by those skilled in the art of the present application. In addition, any terminology used is only for the purpose of describing specific embodiments and is not intended to limit the present application.
[0020] In addition, in order to better illustrate the present application, numerous specific details are given in the following specific embodiments. It should be understood by those skilled in the art that the present application can also be implemented without certain specific details. In some examples, methods, means, components and circuits well known to those skilled in the art are not described in detail in order to highlight the subject matter of the present application. Example 1
[0021] A high-strength, corrosion-resistant glass-lined material for a chemical reactor, the glass-lined material comprising the following components in parts by weight: Al 2 O 3 6.2 parts, SiO 2 69 copies, B 2 O 3 12.5 servings, Na 2 O 2.3 parts, K 2 O 2.7 parts, Li 2 O 1.1 parts, CaF 2 6.5 parts, HfO 2 0.95 parts, ZrO 2 8.4 parts, CoO 0.7 parts, NiO 2.2 parts, Li 2 B 4 O 7 0.66 parts, BaMoO 4 0.87 parts, Sb 2 O 3 1.7 parts, V 2 O 5 4.2 parts, TiO 2 4.1 parts, SrO 0.3 parts. Example 2
[0022] A high-strength, corrosion-resistant glass-lined material for a chemical reactor, the glass-lined material comprising the following components in parts by weight: Al 2 O 3 7.2 parts, SiO 2 68.7 copies, B 2 O 3 13.2 servings, Na 2 O 2.6 parts, K 2 O 2.1 parts, Li 2 O 0.88 parts, CaF 2 6.2 parts, HfO 2 0.98 parts, ZrO 2 8.7 parts, CoO 0.62 parts, NiO 2.5 parts, Li 2 B 4 O 7 0.53 parts, BaMoO 4 0.67 parts, Sb 2 O 3 1.24 parts, V 2 O 5 4.6 parts, TiO 2 5.5 parts, SrO 0.33 parts. Example 3
[0023] A high-strength, corrosion-resistant glass-lined material for a chemical reactor, the glass-lined material comprising the following components in parts by weight: Al 2 O 3 7.9 parts, SiO 2 71.5 copies, B 2 O 3 12.8 servings, Na 2 O 1.5 parts, K 2 O 2.7 parts, Li 2 O 1.33 parts, CaF 2 6.52 parts, HfO 2 0.99 parts, ZrO 2 8.85 parts, CoO 0.83 parts, NiO 2.46 parts, Li 2 B 4 O 7 0.45 parts, BaMoO 4 0.71 parts, Sb 2 O 3 1.3 parts, V 2 O 5 4.8 parts, TiO 2 6 parts, SrO 0.2 parts. Example 4
[0024] A high-strength, corrosion-resistant glass-lined material for a chemical reactor, the glass-lined material comprising the following components in parts by weight: Al 2 O 3 8 parts, SiO 2 69.3 copies, B 2 O 3 13.9 servings, Na 2 O 1.2 parts, K 2 O 2.2 parts, Li 2 O 1.46 parts, CaF 2 6.67 parts, HfO 2 0.91 parts, ZrO 2 8.2 parts, CoO 0.95 parts, NiO 2.5 parts, Li 2 B 4 O 7 0.6 parts, BaMoO 4 0.74 parts, Sb 2 O 3 1.73 parts, V 2 O 5 4.56 parts, TiO 2 4.24 parts, SrO 0.51 parts. Example 5
[0025] A high-strength, corrosion-resistant glass-lined material for a chemical reactor, the glass-lined material comprising the following components in parts by weight: Al 2 O 3 7.5 parts, SiO 2 71.8 copies, B 2 O 3 14 servings, Na 2 O 1.6 parts, K 2 O 2.7 parts, Li 2 O 1.1 parts, CaF 2 6.9 parts, HfO 2 0.81 parts, ZrO 2 8.9 parts, CoO 0.51 parts, NiO 2.93 parts, Li 2 B 4 O 7 0.65 parts, BaMoO 4 0.86 parts, Sb 2 O 3 1.77 parts, V 2 O 5 4.34 parts, TiO 2 5.62 parts, SrO 0.5 parts. Example 6
[0026] A high-strength, corrosion-resistant glass-lined material for a chemical reactor, the glass-lined material comprising the following components in parts by weight: Al 2 O 3 7 parts, SiO 2 70 copies, B 2 O 3 13 servings, Na 2 O 2 parts, K 2 O 2.5 parts, Li 2 O 1.2 parts, CaF 2 7 parts, HfO 2 0.9 parts, ZrO 2 8.5 parts, CoO 0.75 parts, NiO 2.5 parts, Li 2 B 4 O 7 0.6 parts, BaMoO 4 0.8 parts, Sb 2 O 3 1.6 parts, V 2 O 5 4.5 parts, TiO 2 5 parts, SrO 0.4 parts. Example 7
[0027] A high-strength, corrosion-resistant glass-lined material for a chemical reactor, the glass-lined material comprising the following components in parts by weight: Al 2 O 3 7.2 parts, SiO 2 70.3 copies, B 2 O 3 12.8 servings, Na 2 O 2.5 parts, K 2 O 2.7 parts, Li 2 O 1.13 parts, CaF 2 7.3 parts, HfO 2 0.96 parts, ZrO 2 8.2 parts, CoO 0.9 parts, NiO 2.4 parts, Li 2 B 4 O 7 0.66 parts, BaMoO 4 0.76 parts, Sb 2 O 3 1.84 parts, V 2 O 5 4.87 parts, TiO 2 5 parts, SrO 0.21 parts. Example 8
[0028] A high-strength, corrosion-resistant glass-lined material for a chemical reactor, the glass-lined material comprising the following components in parts by weight: Al 2 O 3 6.5 parts, SiO 2 70.9 copies, B 2 O 3 13.7 servings, Na 2 O 1.6 parts, K 2 O 2.4 parts, Li 2 O 1 part, CaF 2 7 parts, HfO 2 0.91 parts, ZrO 2 8.8 parts, CoO 0.79 parts, NiO 2.47 parts, Li 2 B 4 O 7 0.56 parts, BaMoO 4 0.87 parts, Sb 2 O 3 1.73 parts, V 2 O 5 4.22 parts, TiO 2 5.81 parts, SrO 0.36 parts. Example 9
[0029] A high-strength, corrosion-resistant glass-lined material for a chemical reactor, the glass-lined material comprising the following components in parts by weight: Al 2 O 3 7.6 parts, SiO 2 71.2 copies, B 2 O 3 14 servings, Na 2 O 2.98 parts, K 2 O 2.63 parts, Li 2 O 1.15 parts, CaF 2 7.3 parts, HfO 2 0.94 parts, ZrO 2 8.58 parts, CoO 0.92 parts, NiO 2.43 parts, Li 2 B 4 O 7 0.69 parts, BaMoO 4 0.66 parts, Sb 2 O 3 1.91 copies, V 2 O 5 4.64 parts, TiO 2 4.4 parts, SrO 0.53 parts. Example 10
[0030] This example is used to examine the performance of the above glass-lined materials as glass-lined base glaze.
[0031] 1. Test steps
[0032] 1.1 Pretreatment of steel plates
[0033] The same batch of steel plates were selected as the substrate and placed in a muffle furnace, and kept at 600°C for 120 minutes. Sandblasting was performed using a sandblasting machine.
[0034] 1.2 Glaze spraying
[0035] Prepare 40g of glaze according to the formula of Example 1 to Example 9, add 18ml of deionized water and mix evenly to obtain a mixed glaze; stir the mixed glaze on a magnetic stirrer for 20 minutes so that the additives are evenly dispersed in the solution. Pour the evenly dispersed glaze into the spray gun, and keep the spray gun about 30-40cm away from the steel plate during spraying. The speed of moving the spray gun needs to be kept at a constant speed during the spraying process. After spraying, place the steel plate at room temperature and let it stand for 24 hours until the glaze on the surface of the steel plate is completely dry. Dry for 24 hours after spraying the glaze.
[0036] 1.3 Enameling
[0037] Starting from 20℃, heat up to 150℃ after 45min, keep warm for 30min, then heat up to 650℃ after 45min, keep warm for 30min, then heat up to 750℃ after 40min, keep warm for 35min, then heat up to 900℃ after 35min, keep warm for 50min; starting from 900℃, cool down to 750℃ after 45min, then starting from 750℃, cool down to 600℃ after 30min, then turn off the electric furnace and cool naturally to room temperature with the furnace.
[0038] 2. Bending strength test
[0039] A three-point bending test is used, that is, a rectangular or circular specimen is placed on a bending device, an appropriate span is adjusted, and a load is added to the specimen to perform a bending test until the specified bending degree is reached or a fracture occurs.
[0040] First, pre-treat the glass-lined sample by marking it to determine its center point, then polish the center with sandpaper, and then attach the strain gauge to the determined center point.
[0041] Connect the strain gauge of the glass-lined sample to the strain meter, and place the glass-lined sample on the bending tester with the glaze surface facing down and the steel plate facing up. Use a computer to control the tester to descend at a rate of 0.5mm / min and apply a load to the glass-lined sample until the sample reaches a certain degree of bending.
[0042] The maximum bending strength calculation formula of glass-lined specimen is: P=3FL / 2bh 2 .
[0043] In this formula: P is the maximum bending strength of the specimen, in MPa; F is the maximum load value when the specimen breaks, in N; L is the span of the universal testing machine, in mm; b is the width of the glass-lined specimen, in mm; h is the thickness of the glass-lined specimen, in mm.
[0044] The experimental results are shown in Table 1 below:
[0045]
[0046] 3. Fracture toughness test
[0047] The three-point bending test is also used to test the fracture toughness. Under the applied load, due to the continuous change of displacement, a significant peak will be generated, followed by a short-term sudden change in the pressure value, called ΔF, and the corresponding displacement is called ΔX. The greater the difference between ΔF and ΔX, the greater the fracture toughness of the glass-lined sample.
[0048] The indenter of the universal testing machine moves downward at a speed of 0.5mm / min. As the displacement increases, when the indenter begins to contact the bottom of the steel plate, due to the reaction principle of force, the indenter will be supported by the steel plate. However, as the external pressure continues to increase, the compression value of the steel plate will reach its limit. If the pressure continues to increase at this time, the steel plate will resist the pressure by deforming, and the glass enamel layer on its surface will also begin to deform, causing the glass enamel to break until it breaks completely after a period of time, and the experiment ends.
[0049] The experimental results are shown in Table 2.
[0050]
[0051] 4. Hardness test
[0052] The indentation test is used for testing. The main experimental equipment is a Vickers indenter, which is a regular tetrahedron with two opposite faces with an angle of 136°. The diamond indenter is pressed into the surface of the material, and elastic and plastic deformations occur as the load increases. After unloading, the elastic deformation is restored, and indentation marks formed by plastic deformation remain on the surface of the material. The diameter of the concentric circles centered on the indentation is observed and measured using a metallographic microscope to approximately estimate the area of the indentation, and the Vickers hardness (HV) is calculated using the following formula.
[0053] HV=0.102×F / S=0.102×(2Fsin(α / 2)) / d 2
[0054] Wherein, F is the applied indentation load, in N; α is the angle between the opposite faces of the diamond regular tetrahedron indenter, which is 136°; d is the diameter of the concentric circle of the indentation, in mm.
[0055] A relatively smooth area is determined on the surface of the glass-lined sample in advance, and an external force load is applied to the area through the indenter. Through multiple attempts, the indentation produced by the same sample under different external force loads is observed, and it is determined that the appropriate external load value is about 4kg, when the indentation is clearer, and it is maintained for 5s. All glass-lined samples are tested for hardness under this condition.
[0056] The experimental results are shown in Table 3 below:
[0057]
[0058] 5. Corrosion resistance test
[0059] Glass enamel is an amorphous solid with an irregular structure composed of silicon-oxygen tetrahedrons. Therefore, the corrosion process on its surface is very similar to that of glass corrosion. The main reasons are the exchange of surface ions and the erosion and dissolution of the silicon-oxygen network skeleton. When the glaze layer is corroded by acid, the hydrogen ions in the acid first replace the monovalent and divalent metal ions in the solution. As the metal ions continue to precipitate, silica gel or hydrated silicate is adsorbed on the surface of the porcelain layer to form a protective film. This protective film can effectively prevent the acid from further penetrating and corroding the inside of the porcelain layer, thereby achieving the effect of acid corrosion resistance. On the contrary, under alkaline conditions, silicon dioxide will react violently with sodium hydroxide to generate a water-soluble alkaline silicate, which completely dissolves the silicon-oxygen tetrahedral network structure, destroys the integrity of the porcelain layer, and reduces the chemical stability accordingly.
[0060] Weigh the fired samples and place them in 30vol% sulfuric acid solution. Similarly, place two groups in 1mol / L sodium hydroxide solution and seal them with plastic wrap to ensure that all variables except the mass fraction remain consistent and do not change in each beaker. In this experiment, take them out after 240h of corrosion, dry them, and calculate the remainder relative to the initial weight.
[0061] The experimental results are shown in Table 4 below:
[0062]
[0063] The above experimental results show that the present invention significantly improves the hardness, bending strength and fracture toughness of the glass-lined sample, and has excellent acid and alkali corrosion resistance. Among them, the technical effect of Example 4 is the most outstanding.
[0064] In summary, after reading this detailed disclosure, it will be apparent to those skilled in the art that the aforementioned detailed disclosure may be presented only by way of example and may not be restrictive. Although not explicitly stated herein, it will be appreciated by those skilled in the art that this application is intended to encompass various reasonable changes, improvements and modifications to the embodiments. These changes, improvements and modifications are intended to be proposed by this application and are within the spirit and scope of the exemplary embodiments of this application.
[0065] It should be understood that in the foregoing description of the embodiments of the present application, in order to help understand a feature and to simplify the present application, the present application combines various features into a single embodiment or its description. However, this does not mean that the combination of these features is necessary, and it is entirely possible for those skilled in the art to extract some of the features and understand them as separate embodiments when reading the present application.
[0066] It should be understood that the embodiments disclosed herein are illustrations of the principles of the present application. Other modified embodiments are also within the scope of the present application. The embodiments disclosed herein are merely examples and not limitations, and the embodiments of the present application are not limited to the embodiments precisely described above.
Claims
1. High-strength, corrosion-resistant glass-lined material for chemical reactors, characterized by: The composition includes the following components in parts by weight: 8 parts of Al2O3, 69.3 parts of SiO2, 13.9 parts of B2O3, 1.2 parts of Na2O, 2.2 parts of K2O, 1.46 parts of Li2O, 6.67 parts of CaF2, 0.91 parts of HfO2, 8.2 parts of ZrO2, 0.95 parts of CoO, 2.5 parts of NiO, 0.6 parts of Li2B4O7, 0.74 parts of BaMoO4, 1.73 parts of Sb2O3, 4.56 parts of V2O5, 4.24 parts of TiO2, and 0.51 parts of SrO.
Citation Information
Patent Citations
Low-temperature corrosion-resistant glaze material used for enamel pipe
CN105948495A
Dual-side enamel fish-scaling resistant ceramic ground glaze for Corten steel
CN106186690A
Glass lining ground coat based on composite adherence promoter and preparation method of glass lining ground coat
CN117510073A